0132 Sex Differences in Evening Food Intake and Associated Weight Gain During Insufficient Sleep. (27th May 2020) - Withrow, D; Depner, C M; Boland, E M; Birks, B R; Melanson, E L; Higgins, J; Eckel, R H; Perreault, L; Bergman, B C; Wright, K P
Abstract: Introduction: Timing of food intake has emerged as a novel risk factor for weight gain and obesity. Higher evening food intake, especially during insufficient sleep, is associated with weight gain. We aimed to explore initial changes in evening food intake and the respiratory quotient (RQ) during insufficient sleep and subsequent weight gain. We also explored sex differences. Methods: 28 healthy adults (14F) aged 26.3±4.5y completed a 14–16 daylong laboratory protocol. In their home environment participants maintained one week of 9h/night sleep schedules and consumed energy balanced diets for 3 days prior to completing the laboratory protocol. The laboratory protocol consisted of 3 baseline days of 9h/night scheduled sleep with energy balanced diets followed by 10 days of 5h/night scheduled sleep with ad-libitum food intake, with (n=14) and without (n=14) weekend recovery sleep. RQ was assessed on days 3 and 5 in a whole room calorimeter. Evening (dinner and after-dinner snacks) energy intake and body weight were assessed daily. Results: A significant sex by condition effect was observed for evening food intake such that men and women were similar at baseline, but men ate more than women during insufficient sleep, when controlling for body mass (p<0.05). A significant sex by condition effect was also observed for RQ with women showing similar RQ during baseline and insufficient sleep and men showing a higher RQ during insufficient sleep versus baseline (p<0.05). Linear regression with food intake and RQ as predictors of weight gain showed that increased evening food intake, but not RQ, on the second day of sleep restriction was associated with weight gain in men, but not women, at the end of the study eight days later (p<0.05). Conclusion: Findings suggest that rapid changes in evening food intake during insufficient sleep contributes to subsequent weight gain during sustained insufficient sleep, especially in men. Support: NIH HL109706, DK111161, TR001082, DK048520, Sleep Research Society Foundation grant 011-JP-16 and Office of Naval Research MURI (N00014-15-1-2809).